Together: design guidelines for intergenerational playgrounds - Fitzgerald, Mikala (Kansas State University, 2021)
Play is done for joy, as an escape from everyday activities. Not only is play fun, but it also provides participants of all ages with social, emotional, and physical benefits that can last for a lifetime (Rainwater, 1922; Gray, 2017). Playgrounds are a facilitator for play, allowing users to participate in various activities that encourage an active lifestyle and mental wellness (Frost, 2009). In the United States however, public playgrounds are typically designed for specific age groups. The compartmentalization of playgrounds by age group separates users of different generations. Yet, intergenerational connections are essential for strong social equity in communities. Connecting users across generations minimizes hurtful generation-based stereotypes that cause a social divide (Washington et al., 2019). Intergenerational playgrounds can offer play spaces that are welcoming to all ages and provide an opportunity to bring generations together through physical acts of play. Currently, there is minimal research specific to intergenerational playgrounds however, and no known design guidelines that seek to connect people across generations. This research project aims to fill that gap by generating design guidelines and an activity guide for intergenerational playgrounds. To inform the proposed intergenerational playground design guidelines, a review of existing design guidelines related to playground design and intergenerational connections was conducted, along with interviews of subject matter experts. A review of physical fitness recommendations was utilized in combination with precedent studies to understand playground activities and their physical and developmental benefits to each age group. Physical fitness recommendations and precedent studies of playground activities led to the creation of a program activities guide, defining ten playground activities that provide intergenerational connections through physical acts of play. To illustrate the application of the design guidelines and playground activities guide, a projective site design was created for an intergenerational playground at the Martin Luther King Jr. Square Park in Kansas City, Missouri. The projective design shows how a proposed intergenerational playground can provide a space that connects multigenerational users through physical acts of play.
Keywords: Intergenerational playground; Play; Playground; Design; Intergenerational